Generalised Pareto distribution for extreme value modelling in electromagnetic compatibility. Issue 5 (1st February 2013) - Kasmi, C.; Hélier, M.; Darces, M.; Prouff, E.
Abstract : Statistical studies involved in risk management mainly focus on general tendencies which are considered as sufficient for non‐critical applications. This implies laying aside extreme events which may nonetheless be crucial to the security of critical facilities. In light of this observation, it is proposed here to follow the opposite approach and to focus on the extreme values statistics. In particular, it is argued that the approach highlights the benefit of the extremal types theorem from the electromagnetic compatibility point of view.